1990
DOI: 10.1172/jci114932
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant latent transforming growth factor beta 1 has a longer plasma half-life in rats than active transforming growth factor beta 1, and a different tissue distribution.

Abstract: Transforming growth factor,81 (TGF-,B1) is a key regulator of cell growth and differentiation. Under normal physiological conditions, it is made as a biologically latent complex whose significance is unknown. Previous work has indicated that active TGF-,B1 has a very short plasma half-life in rats (Coffey, R. J., L. J. Kost, R. M. Lyons, H. L. Moses, and N. F. LaRusso. 1987. J. Clin. Invest. 80:750-757). We have investigated the possibility that latent complex formation may extend the plasma half-life of TGF-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
163
1
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(175 citation statements)
references
References 26 publications
9
163
1
2
Order By: Relevance
“…TGF-fl has a o, imilar half-life of 2.2 rain in rats [13] and is cleared in the same way as PDGF by binding to cx~-macroglobulin [14,15]. In contrast, recombinant latent TGF-fl does not associate with 0:2-macroglobulin and has an extended plasma half-life of slightly more than 100 rain in rats [16], which is somewhat closer to that which we determined for PD-ECGF.…”
Section: Discussionsupporting
confidence: 74%
“…TGF-fl has a o, imilar half-life of 2.2 rain in rats [13] and is cleared in the same way as PDGF by binding to cx~-macroglobulin [14,15]. In contrast, recombinant latent TGF-fl does not associate with 0:2-macroglobulin and has an extended plasma half-life of slightly more than 100 rain in rats [16], which is somewhat closer to that which we determined for PD-ECGF.…”
Section: Discussionsupporting
confidence: 74%
“…Time point analyses demonstrated that IL-1a mRNA upregulation was rapid, occurring within 30 min of TGF-b exposure, peaked at 1 h and was completely absent within 24 h (data not shown). The kinetics of this gene regulation are consistent with the known half lives of TGF-b and IL-1a mRNA and the fact that TGF-b containing medium needs to be replenished daily to obtain maximum mitogenic stimulation (Turner et al, 1989;Wakefield et al, 1990). To determine if this effect was unique to MCF-10A cells or more broadly applicable, we examined two additional human cell lines previously described to have a growth stimulatory response to TGF-b.…”
mentioning
confidence: 62%
“…This would be in agreement with the latent TGF␤1 complex representing a circulating form of TGF␤1. In support of this idea, it has been shown that the latent complex of TGF␤1 has a serum half-life of 2 h as opposed to a half-life of 3 min observed for the mature active growth factor (15). Formation of latent complexes could thus switch TGF␤ from an autocrine/paracrine mode of action to a more 3.…”
Section: Lap Forms a Molecular Complex With Immobilized Tgf␤1-mentioning
confidence: 96%
“…Indeed, several studies suggest that LAP is a potent inhibitor of bioactive TGF␤ both in vitro and in vivo (6,14). Furthermore, formation of latent complexes increases plasma TGF␤1 half-life about 50-fold (15). Moreover, LAP interacts with the mannose 6-phosphate receptor that has been shown to be required for cellular activation of latent TGF␤1 (16); thus LAP could potentially contribute to enhanced and targeted TGF␤ activity.…”
mentioning
confidence: 99%